Association of previous severe low birth weight with adverse perinatal outcomes in a subsequent pregnancy among HIV‐prevalent urban African women1. Issue 2 (30th November 2016) - Smid, Marcela C.; Ahmed, Yusuf; Stoner, Marie C.D.; Vwalika, Bellington; Stringer, Elizabeth M.; Stringer, Jeffrey S.A.
Abstract: Objective: To evaluate the association between severity of prior low birth weight (LBW) delivery and adverse perinatal outcomes in the subsequent delivery among an HIV‐prevalent urban African population. Methods: A retrospective cohort study was conducted among 41 109 women who had undergone two deliveries in Lusaka, Zambia, between February 1, 2006, and May 31, 2013. The relationship between prior LBW delivery (<2500 g) and a composite measure of adverse perinatal outcome in the second pregnancy was assessed using multivariate logistic regression. Results: Women with prior LBW delivery (n=4259) had an increased risk of LBW in the second delivery versus those without prior LBW delivery (n=37 642). Such risk correlated with the severity of first delivery LBW. The adjusted odds ratio (AOR) was 2.89 (95% confidence interval [CI] 2.05–4.09) for a birth weight of 1000–1499 g, 3.05 (95% CI 2.42–3.86) for a birth weight of 1500–1999 g, and 2.02 (95% CI 1.81–2.27) for a birth weight of 2000–2499 g. Previous LBW delivery also increased the risk of adverse perinatal outcome, with an AOR of 1.4 (95% CI 1.2–1.7). Conclusion: Severe prior LBW delivery conferred substantial risk for adverse perinatal outcomes in a subsequent pregnancy. Abstract : Severe previous low birth weight (LBW) correlated with adverse perinatal outcomes and recurrence of LBW in subsequent delivery in a high HIV‐prevalent urban African population.